Reduction of LDL cholesterol by a monoclonal antibody to PCSK9 in rodents and nonhuman primates. (December 2012) - Gusarova, Viktoria; Howard, Victor G; Okamoto, Haruka; Koehler-Stec, Ellen-Marie; Papadopoulos, Nicholas; Murphy, Andrew J; Yancopoulos, George D; Stahl, Neil; Sleeman, Mark W
Aim: PCSK9 regulates serum LDL cholesterol (LDL-C) by binding hepatic LDL receptor (LDLR) and targeting it to the lysosome for degradation. Fully human monoclonal antibodies were generated against PCSK9 to block its interaction with LDLR and decrease serum LDL-C.Materials & methods: A high affinity human monoclonal antibody, REGN727/SAR236553 (REGN727), was isolated using VelocImmune ® technology and evaluated for effects in relevant animal models.Results: After 8 weeks on a high carbohydrate diet, humanized Pcsk9 hum/hum mice had elevated serum PCSK9 and LDL-C levels. REGN727 effectively reduced LDL-C back to prediet levels. Administration of REGN727 to hyperlipidemic Pcsk9 hum/hum Ldlr -/+ mice led to significantly reduced LDL-C and increased hepatic LDLR levels. Furthermore, administration of a single intravenous dose of REGN727 to normal cynomolgus monkeys reduced serum LDL-C levels by up to 75% for >20 days.Conclusion: Based on these preclinical findings, REGN727 may provide an effective treatment for hypercholesterolemia. Further clinical investigations are ongoing.